Development of Science Literacy-Based E-Booklet Accompanied by Mind Mapping on Human Digestive System Material - Virdana Paduwinata; Ana Yuniasti Retno Wulandari; Badrud Tamam; Eva Ari Wahyuni; Try Hartiningsih (Journal of Education and Learning Research, 2024)
E-Booklet based on science literacy accompanied by mind mapping is a form of the diversity of learning products that can be aligned with the development of technology and information. The purpose of this study aimed to determine the feasibility, response, and readability of a science literacy-based e-booklet accompanied by mind mapping on human digestive system material. This type of research is development research with the ADDIE model without the implementation phase. The research subjects included 31 students of class VIII-A and 13 students of class VIII-B. Based on the research that has been done, the average results of the media aspect feasibility test assessment were validity of 1 with a valid category, 92.2% reliability with a very reliable category, and a material aspect validity of 0.99 with a valid category, 100% reliability with a very reliable category. The results of the assessment of student responses and readability of the e-booklet obtained a very good category. It concluded that the use of science literacy-based e-booklets accompanied by mind mapping on human digestive system material is feasible to use in learning.